VERBAL STRATEGIES USED IN OPENING A CONVERSATION IN OFFICE SETTINGS BY ENGLISH AND VIETNAMESE STAFF AND MANAGERS - My, Hoang Tra (VNU Journal of Foreign Studies, 2017)
In interaction, an appropriate opening may help participants create good impression on their interlocutors and make the conversation more effective; however, producing a polite and smooth opening may be a remarkably challenging task. The study, therefore, aims at yielding insights into the process of conversational opening with focus on the description of verbal strategies. The collected data are 60 English and 60 Vietnamese opening sections in scripted dialogues between staff and managers. The method of qualitative content analysis is applied to expose categories of verbal strategies emerging from the data. The results reveal that, compared with English subjects, Vietnamese ones create a much lengthier opening with the use of more number of verbal strategies. Especially, through the process of opening a conversation, English subjects display a formal relationship with work-oriented exchanges whilst Vietnamese ones show a close but respectful relationship with rapport-oriented exchanges.